Conceptual breakthroughs in evolutionary genetics a brief history of shifting paradigms - Avise, John C. (Elsevier, Academic Press, 2014)
Conceptual Breakthroughs in Evolutionary Genetics is a pithy, lively book occupying a special niche--the conceptual history of evolutionary genetics--not inhabited by any other available treatment. Written by a world-leading authority in evolutionary genetics, this work encapsulates and ranks 70 of the most significant paradigm shifts in evolutionary biology and genetics during the century-and-a-half since Darwin and Mendel. The science of evolutionary genetics is central to all of biology, but many students and other practitioners have little knowledge of its historical roots and conceptual developments. This book fills that knowledge gap.